Nonstationary Axisymmetric Motion of an Elastic Momentum Semi-Space under Non-Stationary Normal Surface Movements - Tran Le Thai; D.V. Tarlakovskii (Учёные записки Казанского университета: Серия Физико-математические науки)
An elastic homogeneous isotropic half-space filled with the Cosserat medium has been considered. The deformed state is characterized by independent displacement and rotation vectors. At the initial instant of time and at infinity, there are no perturbations. On the boundary of a half-space, normal displacements have been given. All components of the stress-strain state are supposed to be limited. A cylindrical coordinate system with an axis directed inward into the half-space has been used. With allowance for axial symmetry, the resolving system of equations includes three hyperbolic equations with respect to the scalar potential and the nonzero components of the vector potential and the rotation vector. The components of displacement vectors, rotation angle, stress tensors, and stress moments are related to the potentials by the known relationships.